Novel biomarkers in preeclampsia risk assessment - Antonić, Tamara; Ardalić, Daniela; Vladimirov, Sandra; Marković, Gorica; Cabunac, Petar; Mihajlović, Marija; Miković, Željko; Stefanović, Aleksandra (Archives of Pharmacy, 2022)
Despite significant progress in improving pregnancy outcomes in recent decades, predicting the risk and treatment of preeclampsia are still major challenges in clinical practice. The aim of this study was to examine non-routine biomarkers in preeclampsia risk assessment. The study involved 90 women with high-risk pregnancies, 20 of whom developed preeclampsia by the end of pregnancy. Biochemical parameters were determined between the 12th and 13th weeks of gestation. The results of the study showed that women who later developed preeclampsia had higher concentrations of lathosterol, cholesterol synthesis marker (p <0.05), inflammatory proteins - monocyte chemoattractant protein-1 (MCP-1), and resistin (p <0.01, both), as well as paraoxonase-1 (PON1) activity (p <0.05). Binary logistic regression analysis showed that higher concentrations of lathosterol, MCP-1, resistin, and PON-1 were associated with preeclampsia development. To determine whether the parameters significant in univariate analysis, are independent predictors of preeclampsia, we applied multivariate regression analysis. Clinical markers commonly used in risk assessment (maternal age and body mass index, mean arterial pressure, and uterine blood flow), lathosterol, MCP-1, resistin, and PON-1 were included in the model. MCP-1 and resistin stood out as significant independent predictors of preeclampsia. The diagnostic accuracy of the investigated model was excellent (AUC=0.859). The study results indicated the importance of a multi-marker approach in risk assessment for preeclampsia development.